How Europe can deliver: Optimising the division of competences among the EU and its member states - Stefani Weiss; Friedrich Heinemann; Melissa Berger; Christoph Harendt; Marc-Daniel Moessinger; Thomas Schwab (Bertelsmann Stiftung, 2017)
This study aims to give guidance for a better-performing EU through an improved allocation of competences between the European Union and its member states. The study analyses eight specific policies from a wide range of fields with respect to their preferable assignment. The analysis applies a unified quantified approach and is precise in its definition of "counterfactuals". These counterfactuals are understood as conceptual alternatives to the allocation of competences under the status quo. As such, they either relate to a new European competence (if the policy is currently a national responsibility) or a new national competence (if the policy is currently assigned to the EU). The comprehensive, quantification-based assessments indicate that it would be preferable to have responsibility for higher education and providing farmers with income support at the national level. Conversely, a shift of competences to the EU level would be advantageous when it comes to asylum policies, defence, corporate taxation, development aid and a (complementary) unemployment insurance scheme in the euro area. For one policy - railway freight transport - the findings are indeterminate. Overall, the study recommends a differentiated integration strategy comprising both new European policies and a roll-back of EU competences in other fields.
Keywords: 330